Quantitive Autoradiographic Study of Competence and Deoxyribonucleic Acid Incorporation in Bacillus subtilis - Somma, Sergio (1970)
The relationships among deoxyribonucleic acid (DNA) uptake, transformation, and autoradiographic labeling were investigated. It is shown that: (i) autoradiography is a good method for measuring the total fraction of competent cells able to incorporate transforming DNA; in our best experiment that fraction was 11.5%. (ii) Computation of the fraction of competent cells in a culture of Bacillus subtilis, by comparing the frequencies of single and double transformants for two unlinked markers, gives values which are somewhat different from those obtained by auto-radiography. (iii) On the average, a competent cell of B. subtilis irreversibly takes up from 0.9 × 10(−10) to 1.4 × 10(−10) μg of DNA; this amount represents about 1/55 to 1/35 of the bacterial chromosome weighing 5 × 10(−9) μg, and corresponds to three to six DNA molecules having a molecular weight of 1.6 × 10(7).